Disability benefits and paying for care - Richard Berthoud; Ruth Hancock (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Attendance Allowance and the care component of Disability Living Allowance are paid to nearly four million elderly or disabled people who need to help in their daily lives. In the course of recent debate about financing the growing demand for social care services, the Wanless report (2006) suggested that these disability benefits paid by the social security system should be curtailed, releasing resources that could used by social workers to pay directly for care. This paper uses some new findings about the needs and resources of disabled claimants to comment on that proposal. It considers six issues of principle about the balance between cash and care in the delivery of support to disabled people. A decision to change policy would need to take account of the costs to the losers, as well as of the benefits to the gainers.
Keywords: 330